Prospective Merger Between Car-Parrinello and Lattice Boltzmann Methods for Quantum Many-Body Simulations (Communications in Computational Physics, 2020)
Formal analogies between the Car-Parrinello (CP) ab-initio molecular dynamicsfor quantum many-body systems, and the Lattice Boltzmann (LB) method forclassical and quantum fluids, are pointed out. A theoretical scenario, whereby thequantum LB would be coupled to the CP framework to speed-up many-body quantumsimulations, is also discussed, together with accompanying considerations on thecomputational efficiency of the prospective CP-LB scheme.